CuInS2-Based Quantum Dot Light-Emitting Electrochemical Cells (QLECs) - Frohleiks, Julia; Wefers, Fabian; Wepfer, Svenja; Hong, A-Ra; Jang, Ho Seong; Nannen, Ekaterina (WILEY, 2017)
Quantum dot/electrolyte hybrid light-emitting devices (QLECs) present a novel class of large-area light-emitting devices potentially combining the efficiency, robustness, and color-tunability of colloidal quantum dots (QDs) with the simple device architecture and easy fabrication of light emitting electrochemical cells. In this work, a Cd-free QLEC based on CuInS2/ZnS (CIS/ZnS) core/shell QDs is presented. The impact of the amount of ionic liquid on the QLEC device performance is systematically studied. The introduction of the additional electron injecting/hole blocking ZnO nanocrystal top layer as well as the proper adjustment of the ionic component leads to CIS-based QLECs exceeding 350 cd m(-2) in brightness.
Keywords: IRIDIUM(III) COMPLEXES; RECENT PROGRESS; HIGH-EFFICIENCY; CHARGE-TRANSFER; IONIC LIQUIDS; DIODES; DEVICE; ELECTROLUMINESCENCE; NANOCRYSTALS; POLYMER